Economic integration in a multicone world? - Christian Volpe Martincus; Jennifer Pédussel Wu (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2005)
This paper examines whether economic integration favors countries' convergence into a common cone of diversification. We analyze the manufacturing specialization patterns for a sample of 19 current and potential European Union countries over the period 1963-1998, and assess the impact of integration on their evolution. We perform year-by-year threshold estimations of Rybczynski relationships to identify the diversification cones and then estimate discrete choice models to investigate whether membership in the European Union is associated with a higher probability of being in a same cone. Economic integration in Europe is found to have promoted convergence from lower to higher diversification cones.
Keywords: F11; F15; C2; 330; Multiple Diversification Cones; Convergence; European Integration; Threshold Estimation; Dynamic Probit Models; Wirtschaftsintegration; Internationale Arbeitsteilung; Intraindustrieller Handel; Entwicklungskonvergenz; Schätzung; EU-Staaten